2016
DOI: 10.30935/cedtech/6164
|View full text |Cite
|
Sign up to set email alerts
|

Learner Views about a Distance Education Course

Abstract: The purpose of the study was to investigate the views of learners experienced in the Distance Learning Platform (DLP), which was prepared according to an online course design model. The participants of the study were 19 learners who took the programming languages course (via the DLP for 14 weeks). Before the application, the preparation of the DLP took nearly 500 hours. A pilot study was performed with the learners during the summer school. The design of the DLP was improved through the views of those learners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
2
7
1
Order By: Relevance
“…It could also be stated that the IDU and COMU participants were pleased to use an integrated system and that they found it very useful to watch video-recorded lessons over and over again. As a support to these findings, Durak and Ataizi (2016), in his study, reports that students favor the platforms involving a number of environments. In addition to all these positive features, it was seen that negative situations, though few in number, were expressed by the participants.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 70%
See 1 more Smart Citation
“…It could also be stated that the IDU and COMU participants were pleased to use an integrated system and that they found it very useful to watch video-recorded lessons over and over again. As a support to these findings, Durak and Ataizi (2016), in his study, reports that students favor the platforms involving a number of environments. In addition to all these positive features, it was seen that negative situations, though few in number, were expressed by the participants.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 70%
“…In general, the most important criticism among all the participants was related to the disciplinary problems such as complacency and frivolity, which was followed by lack of interaction. Especially complacency was examined and emphasized in many studies as an element that needs attention (Alexander et al, 2012;Durak & Ataizi, 2016;Roseth et al, 2011).…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
“…The most popular online tutorials of a kind are Udacity, Udemy, Lynda [12] etc. Furthermore, it is worth noting that one of the main benefits of online education is the dynamics of the transmitted knowledge changes [13]. The current development of science and technology is so rapid that new textbooks and manuals do not keep up at this pace.…”
Section: Introductionmentioning
confidence: 99%
“…Technology skilled educators will continue to be integral part of learners' life while technology bridge the physical spaces and time constraints between teachers and learners and distance learning has already been part of many higher learning institutions programmes now. Durak and Ataizi (2020) reported that based on a study conducted, almost all learners felt that distance learning platforms offer great convenience in terms of time and location. Despite advancement of digital technologies, it is important to note that learners vary in their abilities to understand learning materials.…”
Section: Introductionmentioning
confidence: 99%